2001
DOI: 10.1046/j.1365-2699.2001.00621.x
|View full text |Cite
|
Sign up to set email alerts
|

Allozyme variation in Polyommatus coridon (Lepidoptera: Lycaenidae): identification of ice‐age refugia and reconstruction of post‐glacial expansion

Abstract: Aim The effects of glacial disjunctions on intraspecific differentiations are in the focus of phylogeographical studies. Several studies investigate the consequences of post‐glacial expansions from glacial refugia on the composition within major genetic lineages. Location and methods We analysed the geographical pattern of allozyme variation of twenty loci of Polyommatus coridon (Poda, 1761) (Lepidoptera: Lycaenidae) from thirty‐six localities spread throughout large regions of its European range. A total of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
102
2
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(120 citation statements)
references
References 51 publications
15
102
2
1
Order By: Relevance
“…Discussion-The significantly higher levels of genetic diversity in C. mucedo collected from central/southern Europe versus those from northern Europe are consistent with numerous previous studies that have found an inverse relationship between genetic diversity and distance from glacial refugia (e.g., Armbruster et al 1998;Hewitt 1999;Schmitt and Seitz 2001). This may be attributed to leading edge colonization, in which individuals from the northerly limits of the refugia are the first to colonize recently unglaciated regions, and later immigrants cannot easily invade these established populations.…”
Section: Notessupporting
confidence: 89%
“…Discussion-The significantly higher levels of genetic diversity in C. mucedo collected from central/southern Europe versus those from northern Europe are consistent with numerous previous studies that have found an inverse relationship between genetic diversity and distance from glacial refugia (e.g., Armbruster et al 1998;Hewitt 1999;Schmitt and Seitz 2001). This may be attributed to leading edge colonization, in which individuals from the northerly limits of the refugia are the first to colonize recently unglaciated regions, and later immigrants cannot easily invade these established populations.…”
Section: Notessupporting
confidence: 89%
“…In a previous study, we showed that P. coridon colonised our study area from an ice-age refugium in Italy (Schmitt and Seitz, 2001a). Now, we present the analysis of the genetic effects of the postglacial expansion process and their consequences for the identification of possible expansion corridors.…”
Section: Expansions Of Treementioning
confidence: 78%
“…Therefore, the results for this enzyme were excluded from all calculations of genetic Table 1. The northern limit of distribution (Tolman and Lewington, 1998, modified) is indicated by a broken line, the border between the Adriato-and the Ponto-Mediterranean genetic lineages conforming phenotypic differentiation (Schmitt and Seitz, 2001a) is indicated by a dotted line and the distribution range of the Adriato-Mediterranean lineage by a shaded area.…”
Section: Methodsmentioning
confidence: 99%
“…Genetic analyses of the species on the European scale revealed two glacial differentiation centers, western and eastern (Schmitt and Seitz, 2001). This bi-division is best explained by a long period of disjunction in two ice-age refugia, AdriaticMediterranean and Pontic-Mediterranean.…”
mentioning
confidence: 99%